An error analysis of hiragana and katakana writing systems in the learning of Japanese as third language at UiTM / Norhazlina Husin, Nuranisah Tan Abdullah and Aini Aziz - Husin, Norhazlina; Tan Abdullah, Nuranisah; Aziz, Aini (Universiti Teknologi MARA, 2020)
The teaching of Japanese language as third language to foreign students has its own issues and challenges. It does not merely involve only teaching the four language skills. Japanese language has its own unique values. These unique values also tend to differentiate the teaching of Japanese language as a third language from other third language acquisitions. The teaching of Japanese language as third language to foreign students also involves the teaching of its writing system. This makes the teaching of Japanese language rather complicated because Japanese language has three forms of writings, namely: Hiragana, Katakana and Kanji. Students are required to fully understand the Hiragana system of writing first before proceeding to learn the other two forms of writings. The main challenge in the teaching of Japanese writing systems is the time allocated that can be considered as very limited as other language aspects need to be taught too. This, which relates directly to students' factor very much contribute to the challenges foreseen. Students are likely to face problems in understanding and using the writings as they simultaneously need to adhere to the findings teaching and learning schedules. This article discusses on the analysis conducted in terms of the learning of the Hiragana and Katagana systems of writing among foreign students. The discussion in this article is based on the teaching of Japanese language to students of Universiti Teknologi MARA(UiTM), Shah Alam.